ACTIVITY MEASUREMENTS BY KNUDSEN CELL MASS-SPECTROMETRY - THE SYSTEM FE-CO-NI AND IMPLICATIONS FOR CONDENSATION PROCESSES IN THE SOLAR NEBULA - Fraser, D; Rammensee, W (1982)
We report the use of new apparatus for the direct determination of the activities of components in minerals and melts by the measurement of their intrinsic vapour pressures at high temperatures using a Knudsen-cell mass spectrometer combination. The activity coefficients of Fe, Ni and Co have been determined using this technique in binary and ternary Fe-Co-Ni alloys over the temperature range 1200-1650°C. The results show negative deviations from ideality in the Fe-Ni system and both positive and negative deviations in Fe-Co. Activity coefficients determined in the ternary system were used to calculate the compositions of Fe-Ni-Co alloys in equilibrium with a gas of chondritic composition and the results are consistent with the compositions of metallic particles in Ca, Al rich inclusions in chondritic meteorites. © 1982.